Cancer Cachexia: One Step Ahead - Meriggi, Fausto (Reviews on Recent Clinical Trials, 2015)
Cachexia is one of the most common manifestations in advanced cancer patients, but too often it remains under- recognized and under-treated. Starvation is not the same of cachexia. Cachexia is defined by “weight loss >5% over past 6 months in absence of simple starvation or the combination of ongoing weight loss>2% with BMI <20 or sarcopenia”. The pathogenesis of cancer cachexia is not fully understood, but inflammation and an increased catabolic response to a number of cancer-related factors seem to represent the basis of any assumption. Early diagnosis of a pre-cachectic or cachectic state is a key moment for the treatment of this complex syndrome, in order to guarantee an adequate food intake and suitable exercise and to interfere with the inflammatory processes that are typical of cachexia. Therefore, one of the main aims is to identify those patients most likely to develop the syndrome early. A multimodality baseline approach to cancer cachexia addresses reversible clinical contributory factors. There are currently no medicinal products that have a proven efficacy in the medical approach to cancer cachexia. Recently, anamorelin, a synthetic orally active ghrelin receptor agonist, showed promising results, but the best approach to cancer cachexia probably remains an early multimodal interventions consisting in nutritional intervention, exercise and rehabilitation program, and multi-target drug therapies. This review summarizes what we know and what still need to know about cancer cachexia syndrome.
Keywords: Cancer cachexia